2021
DOI: 10.1017/s0954579421001164
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of relationship-based interventions for maltreated children and adolescents: a systematic review and meta-analysis

Abstract: Child maltreatment is characterized by a harmful relational environment which can have negative cascading consequences for the child’s development. Relationship-based interventions may improve maltreated children’s functioning by addressing key aspects of the parent-child relationship at various stages of development. The objective of the current study was to perform a systematic review on relationship-based interventions for maltreated children and a meta-analysis on the impact of these interventions on obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…Notably, no digital programs focused primarily on strengthening the parent-child relationship, and few studies evaluated program impacts on parent-child interaction, despite the health of this relationship being seminal to the future mental health and well-being of both generations. This highlights an important gap in knowledge and practice in universal parenting programs, and is in stark contrast to significant research investments in relational health in high-risk populations (Bergsund et al, 2021). It may be that universal relational programs have been examined in less depth, due to the perceived non-critical nature of these dyads.…”
Section: Relational Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, no digital programs focused primarily on strengthening the parent-child relationship, and few studies evaluated program impacts on parent-child interaction, despite the health of this relationship being seminal to the future mental health and well-being of both generations. This highlights an important gap in knowledge and practice in universal parenting programs, and is in stark contrast to significant research investments in relational health in high-risk populations (Bergsund et al, 2021). It may be that universal relational programs have been examined in less depth, due to the perceived non-critical nature of these dyads.…”
Section: Relational Outcomesmentioning
confidence: 98%
“…The dearth of universal programs focused primarily on strengthening the parent-child relationship is of concern, given health economic evidence highlighting the centrality of this relationship to the well-being of both generations, and the importance of early intervention (Heckman, 2012). This underscores an important gap in knowledge and practice in universal parenting programs, in contrast to significant research investments in relational health in high-risk populations (selective prevention, indicated prevention, and treatment programs) (Bergsund et al, 2021). Finally, there is a lack of clarity in program evaluation and what a robust approach should include before public dissemination (e.g., relational assessment looking at attachment outcomes, interactional quality using observational measures, and longitudinal child development including socioemotional functioning).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Notably, there are indications that in our current decade, researchers are taking up the mantle. In 2023, for instance, in the most recent volume of the journal (Volume 35), we counted eight articles that included a focus on intervention effects, including two meta-analyses (Bergsund et al, 2023;Van IJzendoorn et al, 2023).…”
Section: Developmental Psychopathology and Prevention/ Interventionmentioning
confidence: 99%
“…There are several reasons relational interventions for child maltreatment warrant attention. Microsystem-level parenting processes are proximal to the child, relative to processes at other ecological levels, and they are also malleable targets for prevention programs (Valentino, 2017) one recent meta-analysis demonstrated that relationship-based interventions for maltreated children are associated with large improvements in observed parent interactive behavior (Bergsund et al, 2021). Furthermore, since many victims of child maltreatment remain in or eventually return to their family homes after child welfare investigations, it is important for programs to treat the parent-child relationship and enhance parent-child relational behavior to ensure children's ongoing safety and security (Valentino, 2017).…”
Section: Introductionmentioning
confidence: 99%